SEM Analyses of Fossilized Chondrocytes in the Extinct Birds Yanornis and Confuciusornis: Insights on Taphonomy and Modes of Preservation in the Jehol Biota - Bailleul, Alida M.; Zhou, Zhonghe (Frontiers in Earth Science, 2021)
Calcified cartilage is a vertebrate tissue that has unique characteristics, such as a high percentage of calcification, avascularity and cells with apparently delayed autolytic processes after death. All of these factors suggest that fossilized cartilage may be favorable to exceptional cellular preservation, but little is known about chondrocyte fossilization overall in vertebrate paleontology. To further understand the spectrum of cellular preservation in this tissue, we analyze the morphology and the chemistry of some intralacunar content seen in previously published avian cartilage from the Early Cretaceous Jehol biota (in Yanornis and Confuciusornis). For this, we combine standard paleohistology with Scanning Electron Microscopy (SEM) and Energy Dispersive Spectroscopy (EDS). To better identify some fossilized structures, we also compare them with experimentally decayed and biofilm-invaded avian cartilage. Histological images of the cartilage of Yanornis show structures that resemble cell nuclei within chondrocyte lacunae. An SEM analysis on this cartilage shows that some lacunae are filled with a type of in vivo mineralization (similar to micropetrotic lacunae) and others are filled with small and spherical silicified cells surrounded by an amorphous carbonaceous material. These silicified cells apparently underwent postmortem cell shrinkage and do not constitute cell nuclei. Confuciusornis shows filamentous, non-spherical cells that are mostly made of silicon and carbon. This cell morphology does not resemble that of typical healthy chondrocytes, but based on comparison with decaying, biofilm-infiltrated chondrocyte lacunae from extant material, the most plausible conclusion is that the cells of Confuciusornis were partially autolyzed prior to their mineralization. In Yanornis and Confuciusornis respectively, silicification and alumino-silicification were responsible for chondrocyte preservation; while alumino-silicification and ironization occurred in their soft tissues. This shows that alumino-silicification is quite a common mechanism of cellular and soft-tissue preservation in the Jehol biota. Moreover, the two different chondrocyte morphologies (spherical and filamentous) apparently reflect two taphonomical histories, including different timings of postmortem permineralization (one rapid and one much more delayed). This type of analysis paired with more actuotaphonomy experiments will be needed in the future to better understand the preservation potential of chondrocytes and other cell types in the fossil record.